System for the processing of scintigraphic images. - Infante, O.; Polo, S.; Rodríguez, G. (Revista Mexicana de Ingenieria Biomedica, 1991)
In recent decades, a series of techniques have emerged that have allowed access to physiological and morphological parameters that previously required extremely bloody interventions, or else these parameters could not be evaluated at the time due to the lack of adequate tools for analysis.